A Quorum Sensing Active Matter in a Confined Geometry - Zhou, Yuxin; Li, Yunyun; Marchesoni, Fabio (Chinese physics letters, 2023)
Inspired by the problem of biofilm growth, we numerically investigate clustering in a two-dimensional suspension of active (Janus) particles of finite size confined in a circular cavity. Their dynamics is regulated by a non-reciprocal mechanism that causes them to switch from active to passive above a certain threshold of the perceived near-neighbor density ( quorum sensing ). A variety of cluster phases, i.e., glassy, solid (hexatic) and liquid, are observed, depending on the particle dynamics at the boundary, the quorum sensing range, and the level of noise.